Reorientation of Law Enforcement of Excise Crimes Through the Ultimum Remedium Approach - Sri Olawaty DJ. Suaib; Melki T. Tunggati (Arena Hukum, 2026)
Law enforcement against excise crimes in Indonesia remains ineffective, as the punitive approach (primum remedium) is overly dominant, leading to suboptimal recovery of state losses and increased excise taxpayer compliance. This condition emphasises the urgency of applying the ultimum remedium principle, such as imposing criminal sanctions as a last resort after administrative mechanisms prove ineffective. This research examines legal issues regarding the effectiveness of applying the ultimum remedium principle in excise crimes and the ideal model for its implementation. Previous research by Ramadhan et al. (2024) highlighted ultimum remedium as a means of recovering state losses, while Kartanto et al. (2020) discussed the direction of applying this principle in tax crimes; however, they did not specifically analyse the implementation issues in excise crimes and the reorientation model for their law enforcement. This research also analyses the effectiveness of applying this principle and offers an ideal model formulation. The method used is normative legal research with statutory and conceptual approaches.  Primary, secondary, and tertiary legal materials were analysed using a descriptive-analytical, prescriptive method, involving deductive reasoning and teleological interpretation. The results show that the application of ultimum remedium has been adopted in excise and tax regulations, but it has not been optimal due to limited understanding among apparatus, unclear regulatory parameters, weak inter-agency coordination, and the dilemma between state loss recovery and deterrent effects. Therefore, reformulation is needed through multi-level strategies, strengthening restorative mechanisms, regulatory harmonisation, and an integrated monitoring system. This research contributes to the development of restorative-based fiscal law and opens opportunities for cross-country comparative studies related to fiscal violations.